PENILAIAN KUALITAS AIR DI SUNGAI CISADANE DILIHAT DARI PARAMETER BOD DAN DO - Isti Rahmandani; Diana Irvindiaty Hendrawan; Widyo Astono (Jurnal Lingkungan dan Kota, 2021)
The water quality of the Cisadane River is decreasing downstream with higher levels of pollution. River water quality can be known by measuring several parameters such as BOD and DO parameters. The research time starts from February - June 2021 with a total of 6 sampling points and the purpose of this study is to identify sources of pollutants that have the potential to contaminate the Cisadane River in the middle to downstream segments, analyze water quality. The middle to downstream segment of the Cisadane River is 34 km long and the method used to identify pollutant sources is carried out by conducting field surveys, water quality analysis is carried out in accordance with SNI and compared with quality standards according to PP. 82 of 2001, as well as water quality analysis with BOD and DO parameters. The results of the identification of potential pollutant sources in the middle to downstream segment of the Cisadane River are dominated by settlements, agriculture, industry, and other domestic activities, namely restaurants and stalls. The results of water quality analysis for BOD parameters ranged from 2 mg/L-5.1 mg/L and DO ranged from 5.14 mg/L-7.85 mg/L. For the BOD parameter from all measurement points there are those that meet the quality standard and none meet the quality standard of class 2 (3 mg/L) and the DO parameter meets the quality standard of class 2 (4 mg/L) because the higher the DO value in the water, the solubility oxygen in the water is good.